Vegetable Price Prediction using Adaptive Neuro-Fuzzy Inference System - Hemageetha, N; Nasira, GM (International Journal of Computer Sciences and Engineering, 2025)
The Agricultural sector is a very important one in the developing countries. In agriculture domain it is very difficult to predict the price of the vegetable, so making use of the prediction technique like neural networks the price is predicted. In this paper a prediction model is established with the help of Adaptive neuro-fuzzy inference system and compares the result with other models. The result for the proposed prediction model is more efficient and accurate than other neural network models for predicting the price of the vegetables.